Development of Social Studies Animation Video (S2AV) Teaching Materials on the Material "Plurality of Indonesian Society" for Junior High School Students - Arif, Viky Risnanda; Afnan, Muhammad; Usmiyatun, Usmiyatun; Lestari, Cicik Yuni (Assyfa Learning Journal, 2023)
Teaching materials are a resource for teachers and students to carry out the learning process. Therefore, it is necessary to develop innovative teaching materials that enable students to achieve superior learning outcomes. One of the innovative and creative and interesting teaching materials is the Social Sciences Animation Video-Based Teaching Material (S2AV). In this study, the aim of this study was to commercialize social studies teaching materials by using animated videos as teaching materials for class VIII junior high school students on the subject of "Indonesian Community Plurality". This development research uses the 4-D method (Define, Design, Develop, and Disseminate). The results showed that the S2AV learning media was valid with an average total score of 3.83 based on material expert validation and 3.87 based on media expert validation. The response of the eighth graders was positive (97%).